2017
DOI: 10.13168/cs.2017.0004
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration and Rehydration of an Ion-Leachable Glass Used in Glass-Ionomer Cements

Abstract: Samples of the ionomer glass known as G338 have been heated at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…We have also shown that the glass G338 loses mass on heating but can regain only a fraction of this loss even under high humidity conditions [ 21 ]. The heat-treated glass sets quicker when mixed with polyacrylic acid than the as-received glass but gives a weaker set cement [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also shown that the glass G338 loses mass on heating but can regain only a fraction of this loss even under high humidity conditions [ 21 ]. The heat-treated glass sets quicker when mixed with polyacrylic acid than the as-received glass but gives a weaker set cement [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that the glass G338 loses mass on heating but can regain only a fraction of this loss even under high humidity conditions [ 21 ]. The heat-treated glass sets quicker when mixed with polyacrylic acid than the as-received glass but gives a weaker set cement [ 21 ]. These findings suggest that heat treatment leads to the loss of surface silanol groups on the glass surface and the formation of siloxane groups.…”
Section: Introductionmentioning
confidence: 99%